2023
DOI: 10.21203/rs.3.rs-2971560/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Eight Weeks of Stop-X and FIFA 11+ Kids Warm-Up on Proprioception and Balance in Football Players with Dynamic Knee Valgus

Abstract: Background This study examined the effect of neuromuscular programs on proprioception and balance in athletes with dynamic knee valgus (DKV) defects. Methods The present investigation involved the purposive and random allocation of 45 male soccer players with dynamic knee valgus (DKV) defects into three distinct groups: a control group (n = 15, age = 11.40 ± .74, weight = 36.24 ± 5.31, height = 140.73 ± 3.34, BMI = 19.93 ± 3.74, sport experience = 2.47 ± .52), Fifa11 + kids group (n = 15, age = 11.07 ± .88, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Baba Goltabar and Norasteh (2022) observed a signi cant difference in knee valgus angle, knee exion angle at the end of the landing, and static and dynamic balance between subjects in the control and training groups after eight weeks of the Stop-X program by soccer players [30]. Eslami et al (2023) reported that Stop-X exercises were more effective than FIFA11 + exercises in improving DKV and balance among young football players with knee valgus abnormalities [16]. Similarly, Mohammadyari et al (2023) determined the effect of the Stop-X program on knee valgus and static and dynamic balance in military cadets with DKV defects.…”
Section: Discussionmentioning
confidence: 99%
“…Baba Goltabar and Norasteh (2022) observed a signi cant difference in knee valgus angle, knee exion angle at the end of the landing, and static and dynamic balance between subjects in the control and training groups after eight weeks of the Stop-X program by soccer players [30]. Eslami et al (2023) reported that Stop-X exercises were more effective than FIFA11 + exercises in improving DKV and balance among young football players with knee valgus abnormalities [16]. Similarly, Mohammadyari et al (2023) determined the effect of the Stop-X program on knee valgus and static and dynamic balance in military cadets with DKV defects.…”
Section: Discussionmentioning
confidence: 99%